The Effect of Ear of Information Reception on the Proficiency of Simultaneous Interpretation - Lambert, Sylvie (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1993)
AbstractIn an attempt to bring together information about simultaneous interpretation, on the one hand, and cerebral dominance, on the other, this study examines the relative proficiency of interpreters when processing information received through one ear or the other as opposed to two ears. Eighteen subjects (professional interpreters and interpretation students) simultaneously interpreted spoken passages from L2 to Ll: one passage was presented to the interpreters' left ear, one to their right ear, and one to both ears. Results indicated that interpreters performed significantly better when the message was presented to one ear or the other rather than to both ears. Furthermore, there was evidence suggesting that the left-ear-to-right-hemisphere route yielded the best performance. The results are discussed in terms of the nature of the tasks involved during simultaneous interpretation as well as cerebral dominance among bilingual individuals.